US inflation reduction act demands quick strategic action from the EU - Kerstin Bernoth; Josefin Meyer (DIW Weekly Report, 2023)
In August 2022, the US Congress passed the Inflation Reduction Act (IRA), a comprehensive piece of legislation aiming to stimulate the US economy and to increase its resilience. At an estimated 430 billion euros, it is a massive government investment and spending program in the welfare state, federal infrastructure, climate action, and environmental protection. At the same time, the IRA is intended to secure the USA's leading position as the largest energy producer in the long term, to support the reindustrialization of the US economy, and to provide a strong response to China's economic and technological hegemonic aspirations. The program's design provides enormous incentives and, in some cases, imposes obligations to relocate production to the US. These local content requirements can have a significant impact on the European economy if production is moved from the EU to the US. The IRA requires strategic economic policy responses that the EU has partially already announced, such as easing state aid rules. However, it must also make urgent changes in other areas, especially in the security of supply of critical raw materials.
Keywords: O14; O2; O3; 330; Industrial policy; policy evaluation; technological change